Driving Digital Transformation: How Transformational Leadership Bridges Learning Agility and Digital Technology Adoption in MSMEs - Chwen-Li Chang; Edgar Octoyuda (Ital Publication, 2024)
Objectives: The utilization of technology within an organization is believed to enhance its effectiveness and efficiency. To reap the benefits of technology, MSMEs must adopt digital technology innovation. Individuals and its capabilities within the organization play a significant role in digital technology innovation adoption. This study aims to examine the nexus between learning agility, transformational leadership, and adoption to digital technology innovations. Methods: This study examines the hypotheses involving 203 employees of MSMEs utilizing PLS-SEM. Results: PLS-SEM results show that learning agility and transformational leadership affect digital technology innovation adoption. Accordingly, transformational leadership mediates the connection between learning agility and the adoption of digital technology innovations. Novelty:This research has implications for organizations in adopting digital innovation, where organizations can optimize individual learning agility and utilize transformational leadership styles to persuade employees to adopt digital technology innovation. Furthermore, this research lies in its comprehensive examination of how transformational leadership can amplify the effects of individual learning agility, thereby fostering a more conducive environment for digital innovation within MSMEs. In addition to a comprehensive discussion, this study provides both theoretical and practical guidelines and provides a thorough examination of both aspects. Doi: 10.28991/ESJ-2024-08-04-020 Full Text: PDF